Letter from Marianne Homburger to Georg and Max Bredig, May 7, 1941 - Homburger, Marianne (1941)
Marianne Homburger (1903-1987) asks her father, Georg Bredig (1868-1944), and brother, Max Bredig (1902-1977), to forward a letter to friends. She additionally provides an update on her efforts to secure immigration visas.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977